THE CORRELATION BETWEEN STUDENTS READING SPEED AND STUDENTS READING COMPREHENSION IN NARRATIVE TEXT AT THE SECOND SEMESTER OF EIGHTH GRADE OF MTsS NURUL HUDA BANJARSARI: English - Victa Suhbatur Rosadi Rosadi; Ahmad Saifudin; Tyas Alhim Mubarok (Journal of English Development, 2023)
The purpose of this study was to determine the relationship between students' reading speed and reading comprehension in class VIII narrative texts at MTsS Nurul Huda Banjarsari. This study presented the question, "Is there a significant relationship between the reading speed and reading comprehension of eighth grade MTsS Nurul Huda Banjarsari students?". A total of twenty eighth-grade MTsS Nurul Huda Banjarsari students constituted the population of this investigation. In this research, the researcher employs an explanatory design in this study, because because explanatory design is quantitative research in which investigators measure the degree of relation between two or more variables use the statistical procedure of correlation analysis. Here the research sample is the total sample or saturated sample. This research uses the descriptive method as a methodology. This research employs a test as its instrument, which measures reading speed and narrative text comprehension. As indicated by the r value of 0.74 and the significance level of 0.000, the correlation between students' reading speed and reading comprehension was found to be statistically significant. This value indicates a significant correlation between reading speed and comprehension.